Exosomal microRNAs in Different Disease Activity Status in Systemic Lupus Erythematosus: A Retrospective Study - Xu, Wenyu; Nie, Peiying; Li, Qian; Gu, Bingjie; Ren, Qijie; Chen, Xingguo (Archives of Rheumatology, 2025)
Background/Aims: Differential miRNA expression profiles in the plasma exosomes of systemic lupus erythematosus (SLE) patients were obtained at various disease activity stages and compared with healthy controls. Materials and Methods: Plasma samples were collected from 48 SLE patients with high, medium, and low disease activity and from 20 healthy controls. The sample set was retrospectively analyzed for differences in clinical features. Plasma exosomes were extracted and subjected to comprehensive detection and analysis. Total exosomal RNA was extracted from the 4 groups, and differential expression profiles were analyzed using miRNA chip technology. Results: Significant differences in clinical parameters—including platelet count (PLT), erythrocyte sedimentation rate (ESR), 24-hour urinary protein, and complement C3/C4 levels—were observed among SLE patients with different disease activity levels (all P < .05). Plasma exosomes were successfully isolated and characterized. Microarray analysis identified distinct exosomal miRNA profiles. Notably, let-7a-5p and miR-23a-3p were significantly downregulated in patients with high disease activity compared to those with low activity (fold change > 2, P < .0001), while miR-4532 was markedly upregulated. Correlation analysis showed let-7a-5p expression was positively associated with PLT (r = 0.61) and complement C3 (r = 0.69) and negatively with ESR (r = –0.65). Conversely, miR-4532 was positively correlated with ESR (r = 0.67) and urinary protein (r = 0.56) and negatively with C3 and C4 (both r = –0.67). Conclusion: Differential miRNA expression was identified in the exosomes of SLE patients at various disease activity levels. These findings indicate the crucial role of these miRNAs in the onset and progression of SLE, providing a basis for further investigation of the immunoregulatory functions of exosomes.